EFFECT OF SPATHOLOBUS FERRUGINEUS EXTRACT ON BLOOD GLUCOSE LEVELS AND HISTOPATHOLOGY OF PANCREAS IN DIABETIC MALE RATS - Eliana, Fatima (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION To determine the ability of Spatholobus ferrugineus (SF) extract as an antidiabetic drug. METHODOLOGY The experimental study used 6 groups of male Sprague Dawley rats which were given SF extracts. The first group was the control group without induction of alloxan, the second group was composed of diabetic rats, the third group was composed of diabetic rats that received glibenclamide, the fourth group was composed of diabetic rats that received SF dose of 62.5 mg/kg bw, the fifth group received SF dose of 125 mg/kg bw, the sixth group received SF dose of 250 mg/kg bw. On day 15, blood samples were taken with cardiac puncture. Histology of pancreas was done by staining with HE. RESULTS In the first group, the mean BG level was 172 mg/dL, the second group was 771.83 mg/dL, the third group was 281.17 mg/dL, the fourth group was 518.50 mg/dL, the fifth group was 191.67 mg/dL, and in the sixth group was 223.83 mg/dL. The results of histological examination of the pancreas in the first group showed no necrosis and no edema, the second group had severe pancreatic damage with ample empty space, the third group had necrosis of the pancreas but the percentage of area was relatively reduced and narrower, the fourth group also had necrosis, the fifth group has begun to see tissue repair, and in the sixth group islet space is almost invisible. CONCLUSION SF extract has a significant effect on the decrease in BG levels seen at a dose of 125 mg /kg bw.